The Potential of Low Glycemic Index Meals as a Factor to Enhance Endurance and to Prevent of Injury in Athlete - Fauzi, Ekha Rifki (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2019)
Background; Endurance is the ability of athlete can do some works to be efficiency and effective in long time where the athlete can feel without more exhausted. Objectives; this review is to describe the studies that showed evidence of LGI to improve endurance performance athlete where can neglect accident of injury. Method; this review used comparative review journal to emphasise for benefit in food of low index glycemic in athletes. Results; Some studies reveal the idea to highlight evidence that LGI meal will give more effect to reduce lactate acid in blood glucose where endurance athlete is more stable than HGI meal. Conclusion; This review also provide the information of benefic LGI meal for health athlete and propose program mechanism LGI meal for people.